Language, culture, and society an introduction to linguistic anthropology - Salzmann, Zdenek; Stanlaw, James; Adachi, Nobuko (Westview Press, 2015)
"For five previous editions, professors have turned to Language, Culture, and Society for its comprehensive coverage of all critical aspects of linguistic anthropology, as well as for its reputation as a pedagogically sound, student-friendly text. Zdenek Salzmann and coauthors James Stanlaw and Nobuko Adachi have revised this classic text with extensive updates and expanded discussions of contemporary issues in the field. This sixth edition continues to be the essential teaching text for the introductory linguistic anthropology course. The sixth edition of Language, Culture, and Society features A greatly expanded discussion of the sociocultural context of language, including gender, race/ethnicity, class, and power dynamics, including a brand-new chapter on gender and a thoroughly revised and broadened chapter on race, ethnicity, and class. An updated chapter-by-chapter resource manual and study guide for students and instructors, including key terms, questions for discussion, group and individual projects, objective study questions and problems (with answers), and suggestions for further reading. More exercises on phonetics and syntax, reflecting contemporary research. Sidebars and boxes throughout the book to provide ethnographic detail, enhance student comprehension of context, and illustrate the practical experience of conducting linguistic research. A global perspective and a focus on transnational and multilingual anthropology Expanded sections on written languages and theoretical and historical perspectives of Linguistic Anthropology. End-of-chapter summary and conclusion sections and a glossary for easy review, as well as an updated bibliography for further research. "--Provided by publisher.